Customer Segmentation Using K-Means Clustering with SPSS Program in a Case Study of Consumer Interest in Current Coffee Shop - Daulay, Risma Yanti; Passalaras, Raja Aulia; Heikal, Jerry (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to segment customers using the K-Means Clustering method in a case study of consumer interest in current coffee shops such as Kopi Kenangan, Kopi Janji Jiwa, Tomoro Coffee, Fore Coffee and Fami Cafe. Customer segmentation is useful for knowing consumer preferences such as interests, background, lifestyle, service quality and consumer characteristics that are useful for knowing the right persona and marketing strategy as well as the value proposition, especially at the Kopi Kenangan, Janji Jiwa, Tomoro Coffee, Fore Coffee and Fami Cafe coffee shops. The analytical method used in this research is data collection by distributing questionnaires to respondents with predetermined criteria in the Jakarta area and outside Jakarta. The questionnaire was distributed in November 2023. The survey results were analyzed using the K-Means Clustering method in the SPSS 23 program to group consumers based on certain attributes such as age, education, domicile, income, occupation, frequently used social media and most popular coffee shop preferences. such as coffee and non-coffee variants, price, service quality and recommending it to other people. Based on the results of K-Means Clustering data processing, there are 3 clusters, namely cluster 1 (Consumptive Customer), cluster 2 (Standard Young Customer), cluster 3 (Potential Customer) which can be concluded that cluster 3 is a potential cluster that is the target of this research, where cluster 3 consists of respondents who are coffee fans and don't like coffee but are very active in using social media and have made online food transactions and always dine in when making transactions at coffee shops. So it can be seen that cluster 3 can be explored and used as a marketing target by carrying out promotions on various social media applications by offering various choices of coffee and non-coffee variants in order to attract customers who don't like coffee so they are interested and want to try the products offered. . The value proposition for current coffee shops is to give the impression of Coffee Vibes and focus on providing a unique and unforgettable coffee experience by presenting innovative flavor variants and creative coffee presentations, exploring new flavors and offering premium quality that can be enjoyed by all groups and creating an atmosphere comfortable and Instagram- worthy to provide a pleasant customer experience that fits the rhythm of modern life. Keywords: Cluster Analysis, Current Coffee, Customer Segmentation, K-Means SPSS,.